Windows 8 and Windows Phone 8 Game Development - Dawes, Adam (Apress Imprint: Apress, 2013)
Creating fun, sophisticated games for Windows devices large or small has never been easier! With masses of example code and fully working games for you to download and run straight away Windows 8 and Windows Phone 8 Game Development is your ideal first step into modern games development. This book gives you everything you need to realize your dreams and produce fantastic games that will run on all Windows 8 devices from desktops to tablets to phones. You can code once and run everywhere. The ubiquity of Windows 8 devices makes this opportunity to good to miss! The Windows 8 and Windows Phone 8 platforms have huge potential for gaming. New form-factors - such as the Surface tablet - coupled with improved processors and higher screen resolutions combine to make Windows 8 the best Windows version yet for independent games development.  It's never been easier to create a fantastic game, package it up and deploy it straight to the Windows Store with its audience of millions. This book will show you how.